2012
DOI: 10.1088/0031-9155/57/17/5485
|View full text |Cite
|
Sign up to set email alerts
|

Automatic localization of vertebral levels in x-ray fluoroscopy using 3D-2D registration: a tool to reduce wrong-site surgery

Abstract: Surgical targeting of the incorrect vertebral level (“wrong-level” surgery) is among the more common wrong-site surgical errors, attributed primarily to a lack of uniquely identifiable radiographic landmarks in the mid-thoracic spine. Conventional localization method involves manual counting of vertebral bodies under fluoroscopy, is prone to human error, and carries additional time and dose. We propose an image registration and visualization system (referred to as LevelCheck), for decision support in spine sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 50 publications
3
89
0
Order By: Relevance
“…The resulting transformation enables the vertebral labels in the CT image to be accurately projected and overlaid in p . The overall framework illustrated in figure 2 is consistent with that in Otake et al (2012, 2013, 2015) and De Silva et al (2016a).…”
Section: Methodssupporting
confidence: 73%
See 3 more Smart Citations
“…The resulting transformation enables the vertebral labels in the CT image to be accurately projected and overlaid in p . The overall framework illustrated in figure 2 is consistent with that in Otake et al (2012, 2013, 2015) and De Silva et al (2016a).…”
Section: Methodssupporting
confidence: 73%
“…Assuming a nominal magnification factor of 2, the volume was downsampled isotropically to a pix /2. The step length for ray casting was chosen to be 2 voxels (equivalently, a pix ) based on a sensitivity study reported in Otake et al (2012). Consistent with Ketcha et al (2016), a soft tissue threshold of 150 HU (shown previously to be insensitive to the particular threshold choice in the range 50 to 300 HU) was applied to the CT image (setting the value to 0 if below) to remove low attenuation regions in the forward projection, and basic overlap of the DRR with the projection image was ensured by translating the CT volume along the longitudinal direction of the patient, thereby determining an initial value for y r , and resulting in an initial registration error of ~20 – 200 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work established a method for fast, robust registration of preoperative 3D images to intraoperative radiography/fluoroscopy, 3,4 demonstrating 3D registration accuracy of target registration error (TRE) <2 mm using only two fluoroscopic views acquired at <20° separation (where 90° separation implies biplane acquisition). 5 The current work extends the registration method to iteratively solve for the rigid transformation ( ) such that a digitally reconstructed radiograph (DRR) from a known component ( C ) yields maximum similarity to intraoperative 2D projections ( f , fixed images, acquired with a C-arm).…”
Section: Methodsmentioning
confidence: 99%